2017
DOI: 10.1111/jvp.12454
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of chlortetracycline in maternal plasma and in fetal tissues following oral administration to pregnant ewes

Abstract: The purpose of this study was to determine if concentrations of chlortetracycline could be detected in fetal plasma or tissues after administering an oral dose of chlortetracycline (CTC; 500 mg/head/day) reported to be effective in controlling Campylobacter spp. abortions. Five pregnant ewes were administered 250 mg/head twice a day (total dose 500 mg/hd/d) for 7 days. On the beginning of day 7, intravenous catheters were surgically implanted or inserted into the fetus and dam. Plasma samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In vitro, C. burnetii is sensitive to several antimicrobial drugs, including tetracycline. In‐feed administration of antimicrobial drugs do not reach target concentrations in reproductive tissues or the fetus . In the face of an outbreak, treatment with two successive injections of oxytetracycline during the last month of pregnancy has been proposed for use in goats .…”
Section: Control Of Coxiellosismentioning
confidence: 99%
“…In vitro, C. burnetii is sensitive to several antimicrobial drugs, including tetracycline. In‐feed administration of antimicrobial drugs do not reach target concentrations in reproductive tissues or the fetus . In the face of an outbreak, treatment with two successive injections of oxytetracycline during the last month of pregnancy has been proposed for use in goats .…”
Section: Control Of Coxiellosismentioning
confidence: 99%
“…6 Area under the moment curve from time 0 to infinity. 7 Mean residence time. 8 Slope of the terminal (elimination) phase.…”
Section: Plos Onementioning
confidence: 99%
“…The only antibiotic approved to treat or prevent campylobacter abortion in sheep is chlortetracycline [5]. However, the vast majority of recent US C. jejuni isolates are reported to be resistant to tetracyclines (including chlortetracycline), and pharmacokinetic studies have shown that feeding chlortetracycline to sheep at the approved dose (80 mg/head/day), or at an even higher, unapproved dose (500 mg/head/day), resulted in levels that were presumed to be subtherapeutic in pregnant ewe plasma and largely undetectable in fetal tissues and amniotic fluid [1,[6][7][8][9]. Results of these studies indicate that feeding chlortetracycline is unlikely to provide therapeutic benefit during an outbreak of C. jejuni abortion in US flocks.…”
Section: Introductionmentioning
confidence: 99%
“…Catheters were surgically placed in the fetus using a previously described procedure (Washburn, Sawant, Lunde, Wu, & Cudd, 2013;Washburn et al, 2018). In brief, a ventral midline laparotomy was performed, the uterus was externalized and incised, and a fetal hindlimb was exteriorized.…”
Section: Surgical Instrumentationmentioning
confidence: 99%
“…Reports of resistance and lack of efficacy have prompted investigation of the pharmacokinetics of the common feed‐additive chlortetracycline. Feeding chlortetracycline to sheep at the approved dose and at the higher, unapproved dose results in subtherapeutic levels in pregnant ewe plasma and mostly undetectable levels in fetal tissues and amniotic fluid (Washburn et al., , ). Chlortetracycline in feed requires a veterinary feed directive, and extra‐label use or use of increased doses of feed additives is illegal in the United States.…”
Section: Introductionmentioning
confidence: 99%